Do neurocognitive scat3 test scores differ between non-concussed national footballers living with and without disability? a cross-sectional study. Issue 11 (25th May 2017) - Weiler, Richard; Van Mechelen, Willem; Fuller, Colin; Ahmed, Osman; Verhagen, Evert
Abstract : Objective: To determine if cross-sectional differences exist using SCAT3 scores for non-concussed England footballers with and without disability. Design: Cross-sectional between group comparison of first-time collected SCAT3 scores. Setting: All England team doctors and physiotherapists commenced between 1st August 2013 and 31st July 2014 standardised annual SCAT3 testing on England footballers following the Zurich 2012 concussion guidelines. Participants: A convenience sample of England national football team players (total: 249; male: 174, female: 75), of whom 185 were athletes without disability (male: 119; female: 66) and 64 athletes with disability (male learning disability: 17; male cerebral palsy: 28; male blind: 10; female deaf: 9). Assessment and outcome measures: Comparison between groups of median SCAT3 section scores was made with the non-parametric Mann-Whitney-Wilcoxon ranked-sum test. Main results: Compared to male footballers without disability, male footballers with disability scored significantly higher for total number of symptoms and symptom severity. However, male footballers with learning disability demonstrated no difference with total number of symptoms and scored significantly lower on immediate memory and delayed recall . Male blind footballers scored significantly higher for total concentration and delayed recall. Male footballers with cerebral palsy scored significantly higher on balance testing and significantly lower on immediate memory. Conclusions: The results of this study suggest that significant cross-sectional between-group variability exists in SCAT3 section scores when non-concussed footballers with disability are compared to footballers without disability. Future concussion consensus guidelines should recognise these between group differences and generate separate SCAT3 guidelines for the growing number of elite athletes living with disability. Competing interests: None.